Regional urban environmental quality assessment and spatial analysis - V. Sruthi Krishnan; C. Mohammed Firoz (Journal of Urban Management, 2020)
Rapid urbanization has resulted in sudden degradation of the environmental quality of urban settlements, which are difficult to measure and quantify. The present study attempts to provide an assessment of the environmental quality by developing environmental quality index (EQI) for the Ernakulam district in Kerala, India. The index values are spatially mapped to develop an environmental quality index map for the study area under five different classes namely, very poor, poor, moderate, good, very good. The EQI values are calculated for nineteen composite variables classified under three domains namely, ecological, meteorological, and socio-economic domains. A preliminary statistical analysis and detailed principal component analysis (PCA) were performed to construct the environmental quality index for the study region. This was followed by a spatial mapping and analysis to provide a better understanding of the status of the environmental quality to the local residents, environmental planners, regional scientists and policymakers. The results obtained from the analysis show that the study area has a low overall environmental quality. The region considered in this paper has highlighting features of various settlement patterns, population distributions, and land use distributions, which indicates a clear transition in the environmental quality index of different settlement units. Hence, by selecting this region and observing various number of indicators, the real effect of urbanization on the quality of the environment was projected. The systematic methodological procedure explained in this paper can be used elsewhere also, where the study area has similar characteristics as that of the area considered in this study. The outcome of the study is applicable for present and future urban planning, building construction, land and resource management for a sustainable environment.
Keywords: 710; Environmental quality index (EQI); Statistical methods; Principal component analysis (PCA); Regression analysis